Los railes del exilio : niǫs de Morelia : un éxodo a México : Museo del Ferrocarril / [autoras, Inmaculada García Lozano, M° Dolores Moreno Burgos ; comisarias, Inmaculada García Lozano, M° Dolores Moreno Burgos] - Moreno Burgos, María Dolores (1956-); García Lozano, Inmaculada
Tít. tomado de la cub.